2015
DOI: 10.1007/s10618-015-0427-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a health intervention via user-generated Internet content

Abstract: Assessing the effect of a health-oriented intervention by traditional epidemiological methods is commonly based only on population segments that use healthcare services. Here we introduce a complementary framework for evaluating the impact of a targeted intervention, such as a vaccination campaign against an infectious disease, through a statistical analysis of user-generated content submitted on web platforms. Using supervised learning, we derive a nonlinear regression model for estimating the prevalence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…This was seen in both lower rates of general practitioner influenza-like illness consultations and influenza-confirmed hospitalisations in both 2013/2014 and 2014/2015 in targeted and non-targeted age-groups 23 24. In 2013/2014, there was also evidence of a significantly lower number of primary school absences25 and in influenza-related social media queries26 in primary school pilot areas compared with the non-pilot areas.…”
Section: Other Laiv Programmesmentioning
confidence: 99%
“…This was seen in both lower rates of general practitioner influenza-like illness consultations and influenza-confirmed hospitalisations in both 2013/2014 and 2014/2015 in targeted and non-targeted age-groups 23 24. In 2013/2014, there was also evidence of a significantly lower number of primary school absences25 and in influenza-related social media queries26 in primary school pilot areas compared with the non-pilot areas.…”
Section: Other Laiv Programmesmentioning
confidence: 99%
“…We also deploy nonlinear regression models using Gaussian Processes as previous works have shown that the relationship between query frequencies and disease rates is significantly better captured by a nonlinear function [31,33,34,50].…”
Section: Nonlinear Regressionmentioning
confidence: 99%
“…Existing approaches have routinely used single task models such as regularized regression [17,22,31,43], Gaussian Processes [31,34], and autoregressive frameworks [31,42,47]. Here, we have chosen to apply MTEN [35] and MTGP [11] for the following reasons: (a) EN and GPs have been applied in many text regression [27,44] and disease modeling approaches [31,33,34,55], and (b) the sample sizes we are operating on are limited and no performance gain would have been achieved by deploying neural network structures (such as [16,51,52]). …”
Section: Related Workmentioning
confidence: 99%
“…These traces of disease observations are embedded in search queries [5, 7, 9, 12, 14, 17, 21, 25, 26, 31, 32, 33, 39, 49, 50, 53, 59, 63, 64, 71, 72 73, 77, 78, 81, 85, 87, 90, 97, 103, 104, 109, 119, 126, 127, 131, 132, 141, 142, 144, 146, 157, 158, 162, 163, 166, 168, 169, 170, 173, 177, 179, 180, 182], social media messages [1, 2, 8, 10, 20, 36, 40, 41, 42, 46, 51, 60, 62, 68, 76, 84, 89, 92, 93, 115, 116, 118, 123, 124, 148, 149, 151, 176], web server access logs [57, 79, 101, 105], and combinations thereof [13, 19, 30, 91, 136, 143, 167]. …”
Section: Related Workmentioning
confidence: 99%
“…The disease surveillance work cited above has been applied to a wide variety of infectious and non-infectious conditions: allergies [87], asthma [136, 176], avian influenza [25], cancer [39], chicken pox [109, 126], chikungunya [109], chlamydia [42, 78, 109], cholera [36, 57], dengue [7, 31, 32, 57, 62, 109], diabetes [42, 60], dysentery [180], Ebola [5, 57], erythromelalgia [63], food poisoning [12], gastroenteritis [45, 50, 71, 126], gonorrhea [77, 78, 109], hand foot and mouth disease [26, 167], heart disease [51, 60], hepatitis [109], HIV/AIDS [57, 76, 177, 180], influenza [1, 2, 8, 9, 10, 13, 19, 20, 21, 30, 33, 40, 41, 43, 46, 48, 53, 57, 59, 68, 72, 73, 79, 81, 84, 85, 89, 90, 91, 92, 93, 97, 101, 103, 104, 105, 109, 115, 116, 118, 123, 124, 126, 131, 132, 141, 14...…”
Section: Related Workmentioning
confidence: 99%